TUMBUH MELEWATI TRAUMA: KEKUATAN PSIKOLOGIS PADA ORANG DEWASA DENGAN PENGALAMAN BROKEN HOME - Ulya, Husna Ni’matul; Ilma, Mughniatul; Al Baqi, Safiruddin (ROSYADA: Islamic Guidance and Counseling, 2025)
This study aimed to explore the psychological strengths that enable adults with broken home experiences in childhood to survive emotionally and construct meaningful, stable lives. Using a qualitative approach with Interpretative Phenomenological Analysis (IPA), five adult participants who experienced parental divorce before the age of 15 were interviewed in depth. The analysis produced six major themes reflecting their psychological resilience: (1) self-acceptance, (2) positive relationships, (3) independence, (4) adaptability, (5) life goals and direction, and (6) developing potential. Participants described a transformative journey in which early emotional wounds became the foundation for strength and growth. Self-acceptance emerged through reflection, spiritual grounding, and reframing of guilt. Positive relationships were formed through emotional boundaries, trust-building, and the creation of safe relational spaces. Independence developed through early financial and emotional self-reliance, while adaptability was shaped by sensitivity to change and social flexibility. Participants also demonstrated clear life direction, often driven by the desire to break negative family cycles. Finally, they exhibited strong motivation for continuous learning and self-actualization. These findings challenge deficit-based perspectives on children of divorce and highlight the agency and resilience of survivors. The study offers implications for psychological support systems that emphasize strength-based approaches and post-traumatic growth.